Intangible attributes for higher education choice - Shanka, Tekle; Terigin, Claire (School of Marketing, Curtin Business School, 2009)
The purpose of this report was to assess the intangible attributes of marketing higher education. Results of responses from 362 university students indicated that the "ability to learning new skills essential to entering the workforce" was the most important intangible attribute to students when selecting a higher education institution, followed by the "national and international reputation of the institution", "project management training and experience", "student life of the institution", and "extra courses related to major studies". Intercultural mix and student clubs attributes showed statistically significant differences between groups for gender, country of birth, or country of usual residence. Results are discussed.